Taxation and development : again - Keen, Michael; International Monetary Fund. Fiscal Affairs Department ([Washington, D.C.] : International Monetary Fund, 2012)
Issues of taxation and development, which have long been a central concern of the IMF, have attracted wider and renewed interest in the last few years. This paper reflects on three broad lessons of experience: that developing countries differ vastly in tax matters, and in ways that are less than fully understood; that the history of "big ideas" in guiding tax reform for developing countries is decidedly mixed; and that the value of the emphasis often placed in this context on "informality" is decidedly limited. It also asks whether ideas of "state building" emphasized in some of the recent literature are likely to lead to practical advice much different from that commonly offered now.
Cover; Contents; I. Introduction; II. Developing Countries Differ-Yes, and ...?; Table 1. Tax Performance in Sub-Saharan Africa; III. The Checkered History of Big Ideas; IV. Informality is Not the Issue; V. State Building and Taxation-What's New?; VI. Conclusions; References.
Title from PDF title page (IMF Web site, viewed September 7, 2012).
Includes bibliographical references.
"Fiscal Affairs Department."
"September 2012."
Keywords: Taxation -- Developing countries; BUSINESS & ECONOMICS -- Public Finance; Taxation; Developing countries; Electronic books